Exploring the use of Treadmill Interventions in Children with Obesity: A Qualitative Study - Negi, Neha; Sasanka Sekhar Pradhan (Gayaku Publisher, 2024)
Childhood obesity is a rapidly growing medical problem worldwide, increasing the risk of long-term illnesses such as cardiovascular disease, diabetes, and psychological problems. Despite the many interventions available, physical activity remains crucial in the treatment of childhood obesity. This study explores the experiences of obese children who participate in treadmill-based interventions. This qualitative study, based on in-depth interviews with children and their parents, aims to reveal the benefits, difficulties, and psychological impact of treadmill training in obesity management programs. Themes that emerged included motivation, parental involvement, and the emotional and physical challenges faced by children. The results show that parental support and maintaining long-term motivation are key to the success of this intervention.